Ibn Khaldūn's Epistemology of Natural Science within his Philosophy of History: A Socio-Economic Analysis - Salsabila Dwi Putri; Imam Rasikh Islami; Putri Julianti; Lukmanul Hakim (Journal of Islamic History, 2025)
Abstract Ibn Khaldun, a Muslim who lived in the 14th century and was known as a philosopher and historian, made important contributions to developing social and economic thought, particularly through his famous work, the Muqaddimah. In Ibn Khaldun's view, history is not merely seen as a series of isolated events but as a process influenced by social, economic, and natural factors. One of the main concepts he introduced was 'Natural Science,' which encompasses the study of physical and social factors that influence the development of society. This article explores how Ibn Khaldun viewed the relationship between 'Natural Science' and social and economic development in the context of the philosophy of history. Through an interdisciplinary approach, this concept reveals the idea of the cycle of progress and decline of civilizations influenced by the physical, social, and economic conditions of society. Keywords: Ibn Khaldun, Natural Science, Philosophy of History, Social, Economics Amin, Khairul. 2018. "Badawah & Hadarah: Ibn Khaldun's Concept of Sociology."." Journal of Sociology of Religion 12. doi: http://dx.doi.org/10.14421/. Fathoni, Rifai Shodiq. 2016. "Ibn Khaldun's Philosophy of History." Insight History.Com. Sarah, Yunia. 2020. "Ibn Khaldun's View on the Philosophy of History." UNAND Repository 13. Sriyatno. 2018. History and Social Change: The Intellectual Thought of Ibn Khaldun. edited by A. S. Nugroho. Purwokerto: UM Purwokerto Press. Sujati, Budi. 2018. "CONCEPTION OF THE PHILOSOPHY OF HISTORY AND HISTORICAL THOUGHT ACCORDING TO IBNU KHALDUN." Tamaddun 6. ابن خلدون, عبدالرحمن بن محمد. 2019. مقدمة ابن خلدون. Cairo, Egypt: دار نهضة مصر للنشر, دولي. الأحمد, محمد علي. 2008. "نحو رؤية منهجية مُ وَ اكِ بة في دراسة التاريخ 'ابن خلدون نموذجاً.'" الفكر الإسلامي المعاصر (إسلامية المعرفة سابقا) 13(51):9-38. doi: 10.35632/citj.v13i51.1205. النصافي, سالم جاسر. 2021. "فلسفة التاريخ عند ابن خلدون (ت 808 هـ /1406 م)." مجلة كلية الأدب جامعة بنها. محمد, جواد حسين. 2017. "تأملات في فلسفة ابن خلدون التاريخية." Journal of Al-Qadisiya in Arts and Educational Sciences 17.